Longitudinal occurrence of methylmercury in terrestrial ecosystems of the Tibetan Plateau. (November 2016) - Liu, Yu-Rong; Dong, Ji-Xin; Zhang, Qiang-Gong; Wang, Jun-Tao; Han, Li-Li; Zeng, Jun; He, Ji-Zheng
Abstract: Methylmercury (MeHg), a neurotoxin, is a global concern because of its potential risk to human and ecological health. Elevated mercury (Hg) concentrations were recently reported in the Tibetan Plateau (TP) due to increasing Hg input from distant regions, yet little is known about MeHg production and distribution in the terrestrial ecosystems of the TP. Here, we report longitudinal occurrence of MeHg and the factors regulating net MeHg production in 23 grassland sites from eastern to western TP. The soil MeHg content varied from 0.002 to 0.058 ng g −1, with different distribution patterns between the eastern and western TP. There was a positive correlation between the MeHg concentration and the longitude after 90 °E, which is similar to the distribution patterns of the total mercury (THg), water and organic carbon in this region. Average MeHg concentration in topsoil is generally higher than that in subsoil. Our results show that MeHg concentration in soils of the TP is directly affected by soil water, potential microbial methylators and THg, while indirectly regulated by soil organic carbon through the microbial community and the longitude-dependent precipitation through soil water. Our study suggests that soil water is the most important driver regulating net MeHg production in the grasslands of the TP. These findings have important implications for unraveling the mechanism of net production of MeHg in high-altitude environments. Graphical abstract: Highlights: Relatively high content of soil methylmercury in the eastern Tibetan Plateau. Major factors influencing soil methylmercury content were identified. Soil water content is the primary factor regulating net methylmercury production. Abstract : Soil water, organic carbon and microbial methylators synchronously regulate MeHg production in soils of the Tibetan Plateau.